Drying study of siloxane-PPG nanocomposites - Chaker, J. A.; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Kluwer Academic Publ, 2000)
This is a study of the structural transformations occurring in hybrid siloxane-polypropyleneglycol (PPG) nanocomposites, with different PPG molecular weight, along the drying process. The starting materials are wet gels obtained by the sol-gel procedure using as precursor the 3-(trietoxysilyl)propylisocyanate (IsoTrEOS) and polypropylenglycol bis(2-amino-propyl-ether) (NH2-PPG-NH2). The shrinkage and mass loss measurements were performed using a temperature-controlled chamber at 50 degreesC. The nanostructural evolution of samples during drying was studied in situ by small angle x-ray scattering (SAXS). The experimental results demonstrate that the drying process is highly dependent on the molecular weight of polymer. After the initial drying stage, the progressive emptying of pores leads to the formation of a irregular drying front in gels prepared from PPG of high molecular weight, like 4000 g/mol. As a consequence, an increase of the SAXS intensity due to the increase of electronic density contrast between siloxane clusters and polymeric matrix is observed. For hybrids containing PPG of low molecular weight, the pore emptying process is fast, leading to a regular drying front, without isolated nanopockets of solvents. SAXS intensity curves exhibit a maximum, which was associated to the existence of spatial correlation of the silica clusters embedded in the polymeric matrix. The spatial correlation is preserved during drying. These results also reveal that the structural transformation during drying is governed by capillary forces and depends on the entanglement of polymer chains.
Keywords: hybrid materials; drying process; small-angle X-ray scattering